Purchase intention of Consumers from Melaka towards Mobile Advertising - Goh Mei Ling; Tan Seng Huat; Yeo Sook Fern; Lim Kah Boon (International Journal of Supply Chain Management, 2018)
Acceleration growth in the telecommunication technology especially in mobile devices has resulted to greater new opportunities to the marketing strategies. It thus has led to the current study on the purchase intention of consumers from Melaka towards mobile advertising. A survey was conducted with a set of self-administered questionnaire. A total of 250 respondents was recruited using convenience sampling. The results show that three out of five independent variables examined, namely credibility, irritation and incentive are significant. Informativeness and entertainment were found to have no impact on purchase intention. The regression model is able to explain 73.6% of the variation in consumers purchase intention. This study is able to provide information in relation to factors influencing purchase intention of consumer which has laid a basis in helping the mobile advertisers to develop better strategy of their advertisement.